Market-based instruments in a growth model with dirty and clean technologies - Meireles, M.; Soares, I.; Afonso, O. (Energy Procedia, 2016)
Energy use strongly contributes to CO2 emissions. Since low-carbon technologies help reducing those emissions, attention should be addressed to technological knowledge. Therefore, this paper develops a dynamic general equilibrium growth model with endogenous skill-biased technological change to study the contributions of environmental policies in producing more ecological goods. By solving the transitional dynamics, it is shown that when green firms and green research are supported by policy and/or dirty activities are taxed, technological progress leads to more ecological goods production and environmental quality improvements. Furthermore, a positive change in green environmental quality fosters R&D on ecological goods, increasing their production.